The US-Chinese rivalry in the Middle East region after 2013 - Hassan, Prof. Dr. Shatha Zaki (The International and Political Journal, 2023)
The Middle East is a milestone on the map of the conflict of geopolitical and economic interests between China and the United States, especially when China began to creep strongly towards the top of the international system as a revisionist force in the structure of the system, which made the United States review its policies towards China, and began to shift from the policy of strategic partnership that prevailed after the end of the Cold War at the international level to strategic. This reality will naturally withdraw from the international system to the subsystems, including the Middle East, which receives great attention from each of them, and it is clear from these indicators that China will face the American strategic competition and blockade in its vital field with a policy of balance outside the field, and avoid the United States moving east by moving through giant economic linkages, such as the Belt and Road Initiative, which all pass through the Middle East.